Modal analysis for the assessment of cementless hip stem primary stability in preoperative THA planning. (November 2017) - Rondon, Andres; Sariali, Elhadi; Vallet, Quentin; Grimal, Quentin
Highlights: Mechanical resonance 3D planning for hip replacement surgery is proposed. Modal frequencies and shapes of the implant are computed. Influence of boundary conditions representative of bone-implant contact is reported. Potential modal numerical indicators of stability are proposed. Graphical abstract: Abstract: This numerical vibration finite element (FE) study introduces resonance three-dimensional planning (RP3D) to assess preoperatively the primary stability of a cementless stem for total hip arthroplasty. Based on a patient's CT-scan and a numerical model of a stem, RP3D aims at providing mechanical criteria indicative of the achievable primary stability. We investigate variations of the modal response of the stem to changes of area and apparent stiffness of the bone-implant interface. The model is computationally cheap as it does not include a mesh of the bone. The apparent stiffness of the bone is modeled by springs attached to the nodes of the stem's mesh. We investigate an extended range of stiffness values while, in future works, patient's specific Hounsfield values could be used to define stiffness. We report modal frequencies, shapes, and a ratio of elastic potential energies (rEPE) that quantifies the proximal motion that should be minimum for a stable stem. The modal response exhibits a clear transition between loose and tight contact as area and stiffness of the interface increase. rEPE thresholds that could potentially discriminate preoperatively between stable and unstable stems are given for a Symbios SPS ® size C stem.